Evidence on Animals in the Middle Ages in the Framework of Culture-Historical Paradigm - Monika Milosavljević (University of Belgrade, 2019)
The paper investigates the relationship between archaeological paradigm, fieldwork practice and archaeological records generated in Serbia after the World War II. The issue is the need to revalorize “old” archaeological records in the context of the current theoretical changes and of adaptation of the existing evidence to new research perspectives. These general issues are discussed on the example of culture-historical or traditional approach in Medieval archaeology in the Serbian context.